Erythema multiforme major associated with Cytomegalovirus in an immunocompetent child. - Saddouk, H.; Kaddar, K.; Hormi, O.; Zizi, N.; Dikhaye, S. (European Journal of Pediatric Dermatology, 2024)
Erythema multiforme is an immune-mediated reaction to various factors, mainly infections. Herpes simplex virus and Mycoplasma pneumoniae infections are often implicated. Cytomegalovirus (CMV) infection is generally asymptomatic in healthy subjects, but cases of erythema multiforme secondary to this infection in immunocompetent subjects are rarely described in the literature. We presented an unusual pediatric case of erythema multiforme major associated with cytomegalovirus infection in an immunocompetent child, who responded favorably to antiviral treatment.